Uji Efektivitas Ekstrak Jintan Hitam (Nigella Sativa) Terhadap Pertumbuhan Bakteri Staphylococcus Aureus Pada Medium MHA (Mueller Hinton Agar) - Makmun, Armanto; Surdam, Zulfiyah; Gunawan, Andi Mufida (Window of Health : Jurnal Kesehatan, 2020)
Indonesia is a developing country facing infectious diseases. Staphylococcus aureus is a major pathogen in humans and almost every person who has been infected with Staphylococcus aureus varies in weight, ranging from snacks to weight that can help people. However, given the antibiotic resistance rates, the use of alternative medicinal plants is a safer choice. This study tries to understand the efficacy of black cumin extract in inhibiting the growth of Staphylococcus aureus bacteria. This research is an experimental post-test study using the disc diffusion method to see how to use Black Cumin Extract (Nigella sativa) as an antimicrobial against Staphylococcus aureus in vitro. Black cumin extract obtained the highest inhibition zone at 100% concentration with a mean inhibition zone of 24 mm, while the lowest inhibition zone at a concentration of 25% with an average inhibition zone of 10 mm. A positive control using chloramphenicol antibiotics used a mean inhibition zone of 30 mm that is sensitive to bacterial growth, whereas in negative controls using distilled zone no inhibition is formed. Compared with Staphylococcus aureus bacteria by giving black cumin extract at all concentrations. It is necessary to test the activity of black cumin seeds (Nigella sativa) against other Gram-negative bacteria. We recommend that in the process of making black cumin extract, use of spectrometry tools with the chromatography method to avoid errors in making extracts.